Endangered Plants in Novel Urban Ecosystems Are Filtered by Strategy Type and Dispersal Syndrome, Not by Spatial Dependence on Natural Remnants - Planchuelo, Greg; Kowarik, Ingo; von der Lippe, Moritz (Frontiers in Ecology and Evolution, 2020)
Understanding the contribution of cities to nature conservation is gaining increasing importance with a globally accelerating urbanization and requires insights into the mechanisms that underlie urban distribution patterns. While a considerable number of endangered plant species have been reported for cities, the spatial dependence of populations of these species on natural remnants versus anthropogenic ecosystems is critically understudied due to deficiencies in population distribution data. To which extent endangered species in anthropogenic ecosystems spatially rely on natural remnants is thus an open question. We used a unique dataset of 1,742 precisely mapped populations of 213 endangered plant species in the city of Berlin and related these point data to habitat patches that had been assigned to natural remnants, hybrid ecosystems and novel ecosystems according to the novel ecosystem approach. By applying point pattern analyses (Ripley’s K function, cross K function, cross pair correlation function) we unraveled the spatial dependence of the populations toward the different ecosystem types. Moreover, we tested how plant traits related to plant strategy and dispersal filter for species occurrence across ecosystems. Differentiating populations on anthropogenic sites revealed that populations in hybrid ecosystems spatially depended on natural remnants, but populations in novel ecosystems (i.e. more than a third of all populations) surprisingly didn’t. A conditional inference tree showed that endangered plant species in novel ecosystems are filtered for ruderal strategy type and wind dispersal syndrome, while competitive and stress-tolerant species were mainly confined to natural remnants. Our results highlight the importance of conserving natural remnants as habitats and seed sources of endangered plants. Yet novel urban ecosystems can support many populations of endangered plant species beyond the adjacency to natural remnants, with hybrid ecosystems likely acting as stepping stones. This indicates a specific contribution of urban ecosystems to biodiversity conservation. Since different filters modulate the species pools of different ecosystem types, novel urban ecosystems are not supposed to substitute fully the habitat functions of natural remnants. Our study thus highlights promising opportunities for involving the total range of urban ecosystem types into urban conservation approaches.